ANALISIS PERFORMANSI SUPPLY CHAIN MANAGEMENT MENGGUNAKAN METODE SCOR DAN AHP DALAM PENINGKATAN KINERJA DI ALETA LEATHER - Agustina, Dwi; Suseno (INVANTRI (Inovasi Dan Pengelolaan Industri), 2024)
This study aims to determine the final value of the results of Aleta Leather's supply chain management performance measurement. The data was then analyzed using SCOR and AHP methods. The results showed that the final value of Aleta Leather's supply chain management performance measurement results was 90.11 which was included in the excellent category. This result is obtained from the multiplication of the score value and the weight of selected performance indicators from 16 existing performance indicators. From the results of the analysis, two performance indicators were found that had values below the target, namely planning cycle time and material efficiency (yield). The conclusion of this study is that SCOR and AHP methods can be used to measure the performance of Aleta Leather's supply chain management well. Suggestions for performance improvement are training and development of natural resources, making agreements with suppliers and improving data analysis. Keywords: SCOR, AHP, Performance, Suply chain, Score